RANCANG BANGUN ALAT PENYORTIRAN BARANG OTOMATIS BERBASIS ARDUINO PADA PT WAHANA PRESTASI LOGISTIK SEMARANG - YAN ILMAS PUIMERA; Danang Danang (STEKOM PRESS, 2018)
The purpose of this research is to design goods sorting equipment automatically using ultrasonic sensors, load cell sensors. A valid arduino-based servo motor so that the prototype product sorting device automatically uses ultrasonic sensors and arduino-based load cell sensors can be received by PT Wahana Prestasi Logistik Semarang. The method used in this research is the Research and Development (R&D from Borg and Gall) research method. This research discusses about building a sorting device automatically using ultrasonic sensors, load cell sensors, servo motors, conveyors and arduino. The final product results obtained The prototype product is valid, proven from the ultrasonic sensor, the load cell sensor detects the height of the package, and the weight of the package, the tool will sort the items automatically and know the price to pay, then this prototype product has been declared good and accepted by the user (PT Wahana Semarang Logistics Achievement) through user validation,